Detection of Extended Spectrum β–Lactmase GeneeCTX-M-1 in Escherchia coli and Klebseilla pneumonia Isolated from Urinary Tract Infection of Pregnant Women in Al-Nassyriah City - Saleh Lhwak , Nasser; A.Abbas , Yahya (University of Thi-Qar Journal of Science, 2019)
This study was performed to detect the presence of CTX-M-1 gene in Klebseilla pneumonia and Escherchia coli are that causing urinary tract infections in pregnant women in Al- Nassyriah city , during the period from september (2016) to february (2017). Three hundred and thirty (n= 330) urine samples were collected and cultured on appropriate media for initial isolation. Morphological, conventional biochemical tests and API 20 system were performed to identify the pathological bacteria agents.Ninety samples showed positive culture, the most common isolates were E. coli 57 (63.3%) followed by K. pneumonia 21(23.3%) and 12(13.3%) from other Gram negative bacteria. ESBLs gene CTX-M-1(688 bp) was found in 22 isolates 17/57 (29.8%) in E.coli and 5/21 (23.8 %) in K. pneumonia.